The Influence of Brand Awareness, Electronic Word of Mouth, and Brand Trust on Brand Preference for Richeese Factory Among Gen Z in Surabaya - Siska Amelia; Rizky Dermawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The fast-food industry continues to experience rapid growth, especially with changes in consumption patterns among Gen Z that prioritize convenience and practicality. Richeese Factory, as a local brand, faces challenges in enhancing consumer preferences amidst intense competition. This research aims to examine the influence of Brand Awareness, Electronic Word of Mouth, and Brand Trust on Brand Preference for Richeese Factory among Gen Z in Surabaya City. The research method used is quantitative with a sample of 98 Gen Z respondents aged 17-27 who have purchased or consumed Richeese Factory at least once. The sampling technique employed is purposive sampling, and the data are analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that Brand Awareness, Electronic Word of Mouth, and Brand Trust have a positive and significant effect on Brand Preference. This finding highlights the importance of marketing strategies that focus on increasing Brand Awareness, managing Electronic Word of Mouth, and maintaining Brand Trust. This research also contributes to the understanding of marketing in the fast-food industry and opens opportunities for further research with other variables and expanding the geographical scope.